Analisis Respon Siswa Terhadap Model Pairs, Investigation and Communication (PIC) dalam Pembelajaran IPA - Prasetyaning Astuti Mahayu Ariyawati; Joko Waluyo; Jekti Prihatin (Jurnal Pembelajaran dan Pendidikan Sains, 2017)
This research is a descriptive study that aims to describe and analyze the response of students in science learning model with PIC (Pairs, Investigation and Communication). This assessment was made as a continuation of the research that has been conducted in August - November 2016. Respondents were 30 students of class VIII F SMP Negeri 5 Situbondo. Data collection techniques used by questionnaire (questionnaire) and unstructured interview. The results of the data obtained and analyzed by quantitative descriptive in terms of percentage with the help of Excel for Windows. Percentage data obtained were analyzed by adjusting the existing categories. The results showed that all the aspects contained in the student questionnaire responses showed 85% with very good category. It show that learning Pairs, Investigation and Communication (PIC) received a positive response from students. Based on the results of interviews on a number of students, they are more willing to express an opinion, easier to carry out an investigation / inquiry and easier to understand the concept of learning. Keywords: learning PIC, students’ response, science learning